The road to federalism : finding the middle ground in Nepal, Myanmar and Sri Lanka - Breen, Michael Gerard (2017)
Following the establishment of post-World War II modern nation-states, many Asian countries including Nepal, Myanmar and Sri Lanka sought to nation build on the basis of their dominant ethnic group’s identity, to the exclusion of smaller ethnic groups. There was substantial resistance, leading to civil war and poor development. Minority ethnic groups have demanded federalism and the recognition of their political equality, lest they pursue a secessionist agenda. It is not known why Asian states have been reluctant to institutionalize federalism, nor what causes it to be established in these holding together situations, let alone what type of federalism is more likely to be conducive to establishing political equality and bringing an end to conflict and authoritarianism. This thesis addresses these questions and dissects the lessons and innovations of the institutional responses of Nepal, Myanmar and Sri Lanka to their diversity based challenges. Using a historical institutional methodology and analyzing the critical junctures and intervening path dependencies, I demonstrate the importance of secession risk and infrastructural capacity variables to the establishment of holding together federalism, building on the theories of Riker (1964) and Ziblatt (2004, 2006). I show how the initial nation-building mechanism, as a tool of power reproduction by the dominant ethnic group, kick started a simultaneous reactive sequence leading to centralization, concession and ultimately, a federal compromise. In particular, when the secession risk is moderate, and when minority ethnic groups have a demonstrable infrastructural capacity, there are incentives for regime change agents from the dominant ethnic group to align with minority ethnic groups to pursue mutual goals of federalism and democratic reform. Further, although federalism may be agreed as part of such a constitutional settlement, there remain many issues to resolve, primarily the demarcation of units, the division of powers, power-sharing and proportionality. An ethnic federal system is likely to have a narrower and less secure set of powers for units with any shortcomings in ethnic autonomy addressed by inclusion, non-territorial arrangements, local government and personal laws. Accommodation of diversity is a just goal, but without moderation, accommodation can lead to extremism and undermine political equality. Nepal, Myanmar and Sri Lanka are finding a middle ground whereby deliberative and moderating institutions are combined with accommodating ones to balance centrifugal and centripetal forces. Based on their experiences, I hypothesize that a federal system that encourages, if not requires, multiethnic political parties at the center, and ethnic parties in the units and sub-units provides a range of cross-ethnic, accountable, multilevel and semi-detached forums that incentivize moderation through deliberation, while accepting the validity and justice of ethnic autonomy and other accommodating institutions.